Gambaran Resiliensi Anak Panti Asuhan Ditinjau dari Perbedaan Latar Belakang Keluarga - Zahra Mufatihah; Jelyanah Jelyanah; Rima Ayu Lestari; Anisa Siti Nurjanah (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
Adolescence is a transitional phase toward adulthood characterized by emotional and social challenges, particularly for orphanage adolescents who experience limited family support and the structured dynamics of institutional care. This study aims to explore how resilience develops among orphanage adolescents, examined through Grotberg’s (1999) framework of resilience as the primary analytical lens. Using a qualitative case study design, data were collected through interviews and observations involving two female adolescents living in an orphanage with different family backgrounds. The findings reveal that resilience is formed through three interrelated aspects: I Have, I Am, and I Can. Social support from caregivers and peers fosters a sense of security (I Have), personal strengths such as empathy and self-confidence nurture perseverance (I Am), while communication skills and emotional regulation facilitate positive adaptation (I Can). Overall, the resilience of orphanage adolescents emerges from the interaction between external social support, internal personal strengths, and socio-emotional competencies that enable them to grow into strong, adaptive, and independent individuals.